2013
DOI: 10.1017/s0967199413000439
|View full text |Cite
|
Sign up to set email alerts
|

Expression of INHβA and INHβB proteins in porcine oocytes cultured in vitro is dependent on the follicle size

Abstract: SummaryThe current study aimed to investigate differential expression of inhibin βA (INHβA) and inhibin βB (INHβB) in porcine oocytes before or after in vitro maturation (IVM) isolated from follicles of various sizes. Porcine oocytes isolated from large, medium and small follicles (40 from each) were used to study the INHβA and INHβB protein expression pattern using western blot analysis before or after 44 h of oocyte IVM. An increased expression of INHβA was found in oocytes collected from large and medium fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…In relation to the INHBA gene, previous studies have demonstrated a higher expression in porcine MF‐derived oocytes, than in those derived from SF after IVM (Kempisty et al., 2012) and in protein prior to and after IVM (Kempisty et al., 2015); similar findings were described in the case of MII bovine oocytes compared with GV oocytes (Leal et al, 2011). Our results point to INHBA expression being similar in CCs.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In relation to the INHBA gene, previous studies have demonstrated a higher expression in porcine MF‐derived oocytes, than in those derived from SF after IVM (Kempisty et al., 2012) and in protein prior to and after IVM (Kempisty et al., 2015); similar findings were described in the case of MII bovine oocytes compared with GV oocytes (Leal et al, 2011). Our results point to INHBA expression being similar in CCs.…”
Section: Discussionsupporting
confidence: 53%
“…The studied genes were selected according to their involvement in developmental competence. For example, BMPR2 is the co‐receptor for BMP15 and GDF9, which play fundamental roles in follicular growth, oocyte quality and CC expansion (Chand et al., 2006; Duffy, 2003; Li et al., 2008); LHR and FSHR are LH and FSH receptors, LH regulating meiotic resumption (Jaffe & Egbert, 2017) and FSH being essential for follicular growth and the prevention of atretic antral follicles (Wang & Greenwald, 1993); NR2F6 inhibits LHR (Zhang & Dufau, 2000), although its function remains unclear in CCs, even though orphan nuclear receptors are known to play a role in many reproductive events (Bertolin et al., 2010); INHBA function is thought to be related with oocyte differentiation and follicle growth (Ireland et al., 2009; Kempisty et al., 2015); FST is related with oocyte developmental competence (Patel et al., 2007); CD44 is the main hyaluronan receptor, which is the principal component of CC expansion; CD44 is also involved in the oocyte meiotic resumption (Yokoo et al., 2010); ARID1B is involved in cell cycle regulation (Yan et al., 2008); and VEGFA regulates angiogenesis in the ovary (McFee & Cupp, 2013), the steroidogenesis of granulosa cells (Costermans et al., 2020; Mishra et al., 2017) and oocyte and embryo development (Luo et al., 2002a, 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…The ovulatory gonadotropin surge regulates expression of plasminogen activator family members within the ovarian follicle, which can weaken walls of the Graafian follicle at ovulation . As increased expression of INHβA was found in oocytes collected from large and medium follicles compared with small follicles, INHβA can be recognized as markers of follicle and oocyte maturation . Retinol‐binding protein 4 level, as a putative mediator of insulin resistances, is increased in association with gonadotropin levels in healthy women .…”
Section: Discussionmentioning
confidence: 99%
“…The next gene that showed a decrease in expression after IVM is inhibit subunit beta A (INHBA). It is believed that it plays an important role in reproduction and development through the coding of activins from TGF-beta superfamily [ 84 , 85 ] and is involved in the secretion of FSH from the pituitary [ 86 ], being also a marker of porcine oocyte quality [ 87 ]. A study on boars showed that INHBA is significant in testicular development, especially during puberty [ 88 ].…”
Section: Discussionmentioning
confidence: 99%